The effectiveness of rectal and oral paracetamol in decreasing fever in children - Gama AF Isnaeni Djauhar Ismail Sasmito Nugroho (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: The common treatment to reduce fever is administration of paracetamol orally. However, oral route is sometimes not possible due to some problems, such as vomiting, irritability, unconsciousness, and convulsion and therefore, paracetamol should be administered rectally.Objectives: To know the effectiveness of rectal compared to oral administration of paracetamol in febrile children.Methods: This study was a parallel randomized, double-blind, controlled trial, comparing the effectiveness of rectal paracetamol to oral paracetamol. The study subjects were children with fever. Consecutive sampling was used to collect samples, and block randomization was used for random allocation. The study was conducted from November 1, 2006 to April 30, 2008. The body temperature was measured just before taking the drug (to), and was monitored after 30 minutes (t1), 60 minutes (t2), 90 minutes (t3), 120 minutes (t4), 150 minutes (t5), and 180 minutes (t6). Inferential statistic tests used were chi square, t-test and Mann Whitney U test.Results: A total of 176 subjects eligible for the study were randomly assigned to receive either paracetamol 12.5 mg/kgBW rectally (88 subjects) or paracetamol 12.5 mg/kgBW orally (88 subjects). There were 6 subjects who were drop-out and 1 subject failed from rectal group, and 6 subjects were drop-out and 2 subjects failed from oral group. Paracetamol average dose for each group was 12.5 mg/kgBW. The proportion of the decrease in body temperature to 38°C in the first 30 minutes was significantly higher ??? in oral group. The change in body temperature from initial body temperature between oral and rectal routes after 30 minutes was significantly different (to-t1: p=0.003), but later the decrease was notstatistically different (to-t2: p = 0.471, to-t3: p = 0.488, to-t4: p =0.824, to-t5: p = 0.790, to-t6: p = 0.493): the differences between two periods of measurement were not significant (t1-t2: p=0.073, t2t3: p=0.791, t3-t4: p=0,171, t4-t5: p=0.199, t5-t6: p=0.426), except from to-t1 (p=0.005).Conclusion: Rectal paracetamol 12.5 mg/kgBW had a higher effectiveness compared with oral paracetamol to reduce fever in children.Key words: fever - rectal paracetamol - oral paracetamol - effectiveness